Política y prensa en Costa Rica. El caso del presidente Ricardo Jiménez Oreamuno (1875-1945) - Molina Jiménez, IVÁN (Estudios sobre el Mensaje Periodístico, 2008)
This article analyses the way in which Ricardo Jiménez, three times president of Costa Rica, used mass media to develop a political career characterized by a strategic presence in the public sphere. I argue that Jiménez became the first media figure in Costa Rican history during the 1930´s and 1940´s. To develop the argument I examine diverse stages in Jiménez´s political career as well as his intellectual production and references of him in the press.
Keywords: Politics; Newspapers; Public sphere; History; Costa Rica